Desenvolvimento de uma ferramenta tecnológica para estratificação do risco familiar no território da estratégia saúde da família - Ripardo, José Fábio Cardoso (2023)
The Coelho and Savassi Family Risk Scale (ERF-CS) is a validated instrument of family approach whose application makes it possible to measure the degree of risk and vulnerability of the population assigned to a Family Health Unit (USF), based on markers (risk sentinels) contained in the registration information of users in the Health Information System for Primary Care (SISAB) and in e-SUS Primary Care (e-SUS APS). The objective of this project is to develop a technological tool, supported by mobile devices, for risk stratification and care planning for subsequent families by a USF in the municipality of Crateús - CE. In this regard, we developed a screen application and used an application to stratify the family risk of the study territory population, based on the ERF-CS. The survey showed that 612 families (80.7%) were classified as having usual risk, 65 families (8.7%) as having minimal risk, 43 families (5.7%) as having medium risk and 38 families ( 5%) as maximum risk. In the process, we still had geospatial resources available to map the most independent families in the territory, by carrying out a documentary research whose data sources were the Individual Registration and Home and Territorial Registration forms of e-SUS APS, replaced by community agents of health - ACS. A qualitative investigation was also carried out with the aim of evaluating the usability of the tool by PHC professionals in the municipality. In this way, the development of a canvas application with low code language allowed the creation of an accessible and easy-to-use technological tool, which was able to efficiently stratify risk and family vulnerability. Therefore, it is concluded that all the proposed objectives were successfully achieved.